The use of the mobile phone in the rural zones of Peru - Franciskovic, Jubitza Mariana (2021)
Purpose. The main objective of the research is to examine whether the possession and the consumption of the service of a mobile telephone by the families of rural zones has improved their wellbeing in the last 10 years (2007–2016). Design/methodology/approach. A quantitative analysis of panel data is proposed in order to analyze the effect of the use of the mobile telephone in rural zones by region of Peru during the last 10 years and capture the unobservable heterogeneity during the said period. In this manner, it is hoped to investigate the effect of the increased use of said technology in Peru. Findings. The results obtained show that the increase in the acquisitions of mobile telephones in rural zones has had a positive impact on the wellbeing of households. Continuous business innovation driven by citizens’ needs and the greater accessibility of mobile telephones are the main reasons based on the Peruvian context under study. Originality/value. In Peru, there has been an explosive increase in users of mobile telephones in the last 10 years. The use of this technology may be arriving in rural households before other basic services, provoking individual and social changes and creating new employment and income opportunities. This would support the recent recognition of the mobile telephone as an essential tool for development, especially in underdeveloped countries.